50 activities for diversity training - Lambert, Jonamay; Myers, Selma (Human Resource Development Press, 1994)
The 50 activities in this resource book have been tested with hundreds of participants to ensure their appropriateness and effectiveness for a variety of diversity training needs. Employees at all levels will be stimulated by interactively learning about cultural and gender differences, and mastering new skills for communicating more effectively in our diverse workplaces. Each activity is ready to use and includes trainer's notes and all necessary handouts and overhead transparency masters. They each take between 15 and 45 minutes to complete. Activities Cover: Diversity icebreakers; Change; Communication; Conflict resolution; Gender at work; Culture and career transitions. Training Objectives: Illustrate how cultural differences may impact behavior; Increase awareness of the impact of culture in the workplace; Demonstrate skills for managing a culturally diverse work force; Address issues of gender in the workplace. Training Methods: Icebreakers; Participative exercises; Role-plays; Mini case studies.